A INTERAÇÃO GENÓTIPOS X AMBIENTES IMPACTA A EMISSÃO DE CO₂ DO SOLO EM MILHO? - RENATO NUNES VAEZ (2024)
The research sought to understand the variability of carbon dioxide (CO₂) flow in soils cultivated with different corn hybrids, the objectives include estimating FCO₂, soil moisture and temperature, evaluating the relationship between these variables and corn genotypes. Five maize genotypes were used in the second harvest of 2024 in four different environments, with two environments in Mato Grosso do Sul and two in Goiás being evaluated during three phenological stages of the crop, where the variables analyzed were CO₂ flow (FCO₂), soil moisture and temperature. Soil CO₂ emissions (FCO₂) were measured on site with the EGM-5 portable system, at 10 points per genotype. Soil CO₂ emissions varied according to corn genotypes and environments in the Brazilian cerrado. The genotype-environment interaction showed that some genotypes, such as G1 and G3, had lower emissions. Variables such as temperature and soil moisture influenced CO₂ flow. The selection of specific genotypes for the cerrado emerges as a promising approach to mitigating CO₂ emissions in agriculture.